2016
DOI: 10.1002/ppul.23439
|View full text |Cite
|
Sign up to set email alerts
|

Children with lower respiratory tract infections and serum 25‐hydroxyvitamin D3 levels: A case–control study

Abstract: Children with lower respiratory tract infections in Guatemala had low 25-hydroxyvitamin D levels. Pediatr Pulmonol. 2016;51:1080-1087. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The prevalence of vitamin D deficiency in young children hospitalized with pneumonia in low-middle income countries (LMICs) has been reported to be between 12% to 63% [ 5 , 27 , 28 ], compared with 9.7% to 30% in high income countries [ 18 , 19 , 29 ]. Our finding of 19% is similar to that reported in children from Nepal hospitalized with WHO-defined pneumonia (12% of 568 children studied), with comparable demographic profiles but a higher proportion of participants with danger signs or hypoxemia than in our study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of vitamin D deficiency in young children hospitalized with pneumonia in low-middle income countries (LMICs) has been reported to be between 12% to 63% [ 5 , 27 , 28 ], compared with 9.7% to 30% in high income countries [ 18 , 19 , 29 ]. Our finding of 19% is similar to that reported in children from Nepal hospitalized with WHO-defined pneumonia (12% of 568 children studied), with comparable demographic profiles but a higher proportion of participants with danger signs or hypoxemia than in our study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the molecular structure, 25-OH-D3 is the addition of a hydroxyl group to the 25-position carbon atom of vitamin D3 [ 22 24 ]. However, this addition occurs in the body through a series of biochemical reactions, through the 25-hydroxylase hydroxylation in the mitochondria of liver cells, which then forms 25-hydroxyvitamin D3 [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were as follows: patients with other systemic diseases or serious infectious diseases, patients with incomplete clinical data and information, patients who had recently taken glucocorticoids and other drugs for treatment, and patients undergoing hemodialysis or kidney transplantation were excluded from the study. Regarding the molecular structure, 25-OH-D3 is the addition of a hydroxyl group to the 25-position carbon atom of vitamin D3 [22][23][24]. However, this addition occurs in the body through a series of biochemical reactions, through the 25-hydroxylase hydroxylation in the mitochondria of liver cells, which then forms 25-hydroxyvitamin D3 [25].…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Li et al 21 with 1582 children, the group with community-acquired pneumonia was compared with the control group, and the low 25(OH)-D vitamin level was found to be lower in the group with community-acquired pneumonia. In addition, in a case–control study conducted by Velarde López et al 22 25(OH)-D vitamin deficiency was found to be significantly low in children with lower respiratory tract infections.…”
Section: Discussionmentioning
confidence: 93%